Reklamda özdenetim - Mahmutoğlu, Vildan (My University, 2000)
Reklam, bir mal ya da hizmetin satışını arttıran, insan davranışlarını belirli bir yönde etkilemeyi amaçlayan kitle iletişim teknikleridir. Reklam, en genel tanımıyla, bir olayın, haberin belirli bir insan topluluğuna duyurulmasıdır. Reklamlarda çeşitli mal ve hizmetlerin nereden, nasıl ve ne fiyatla alınabileceği hedef kitleye ,kitle iletişim araçlarıyla iletilir. Reklamcılık, insanların alışverişe başladığı zamanlarda başlayıp, ekonominin ve iletişim araçlarının gelişimine paralel olarak sürekli gelişmiştir. Sözlü reklam olan kafiyeli manilerin yerini, matbaanın icadıyla, kalıcı reklam medyası olan gazeteler almıştır. 19.yüzyılda teknolojideki gelişmeler üretim de kullanılmaya başlanınca sanayiler kurulmuş, üretim fazlalaşmıştır. 'Kütlesel Üretim' beraberinde 'kütlesel tüketim'i getirmiştir. Üretilen malların satılıp tekrar üretilmesi için yeni Pazarlar aranmış, böylece reklamcılık gelişmiştir. Üretim arttıkça rekabet artmış, rekabetin artması da reklamlara yansımıştır. Teknolojik gelişmeler sonucu, reklam medyası farklılaşarak çoğalmıştır. Radyonun ve televizyonun bulunuşuyla yeni ürünler insanlara duyurulup satış artırılmıştır. Osmanlı Devleti'nde ilk reklamverenler ticaretle uğraşanlar reklamverenler olmuştur. Yabancı dilde çıkan gazetelerde Avrupa'daki, özellikle Fransa'daki modern yaşam anlatılıp , modern yaşam için gerekli olan tüketim malları gösterilirdi. Reklamcılık ülkemizde Cumhuriyetin ilanıyla tam olarak gelişmeye başlamıştır. Harf devrimi okuma yazma bilenlerin sayısını artırmış, buna bağlı olarak gazeteler artmış ve reklamverenler kendilerine etkili bir reklam mecrası bulmuşlardır. Ancak Tek Partili dönemde, sanayi ile uğraşan kesim olmadığından ve devletçilik ilkesi uygulandığından rekabet ortamı olmamış dolayısıyla da reklamcılık pek gelişmemiştir. Çok partili hayata geçişle birlikte ekonomide de bir canlılık olmuş, ticaretle uğraşanların sayısı artmıştır. Bu da reklamcılığı olumlu etkilemiştir. Özellikle 1980 den sonra tüketimin artması reklam mecralarının çeşitlenerek çoğalması, rekabet ortamının olması reklamcılığın büyümesinin nedenleridir.1990larda özel televizyonların yayına geçmesiyle, reklam en etkili mecrayı bulmuştur. Devlet televizyonunun ağır yapısından ve denetimden sonra özel televizyonlar reklamcıların kullandığı önemli bir mecra olmuştur. Sanayi Devrimi ile kütlesel üretime geçilmiş , sayı ve çeşit olarak çok fazla mal üretilmeye başlanmıştı. 'Kütlesel üretim' kütlesel tüketim'i doğurmuştur. Günümüz toplumu 'tüketim toplumu' kimliği taşımaktadır. Dünyada ırk,renk,din,siyasal görüş gibi şeylerin farklı kıldığı insanların tek ortak noktaları 'tüketici' olmalarıdır. 'Tüketici' kimliği evrensel bir kimliktir. Herkes tüketici olmasına rağmen tüketici bilinci pek gelişmemiştir. Aldatıcı ve yanıltıcı reklamların etkilediği en büyük kitle tüketici kitlesidir. Bugün tüketici olmak geçmişe oranla daha zordur. Ürünlerdeki çeşitlilik tüketici açısından seçimi zorlaştırmıştır. Tüketicinin bu kadar çeşitlilik içinde seçeceği ürün, reklamını gördüğü üründür. Reklamdan aldığı bilgiye göre seçimini yapar. Bu nedenle reklamlar tam ve doğru bilgi vermelidir. Yanıltıcı bilgi veren, özellikle abartılarak yapılan reklamlar tüketici memnuniyetsizliğine yol açar. Tüketici memnuniyetsizliği ise bir süre sonra reklama olan güvensizliği meydana getirir. Reklamlar tam ve doğru bilgi vermelidir. Doğru , yanıltıcı olmayan reklamlar ekonomi için vazgeçilmez bir öğedir. Yanıltıcı reklam ise ekonomik savurganlığa neden olur. Bu nedenle de reklamlar denetlenir. İki tür reklam denetimi Dünyada ve Türkiye'de uygulanır. Biri devlet tarafından konulmuş yasalara göre yapılan yasal denetim, diğeri ise sektörün toplumsal sorumluluk bilinciyle kendine uyguladığı özdenetimdir. Özdenetim de reklamverenler, reklam ajansları ve mecralar yasal denetime gerek kalmadan kendilerini denetlerler. Özdenetim yasal denetimden daha etkilidir. Çünkü reklam yapanlar reklamı en dikkatli izleyen kişilerdir. Bu nedenle reklamcıları kendilerini denetlemeleri en etkin ve hızlı yoldur. Ülkemizde reklam özdenetimi Reklam Özdenetim kurulu (RÖK)tarafından yapılmaktadır. Her özdenetim yapan ülke de olduğu gibi RÖK'ün de dayanağı Uluslararası Ticaret Odası'nın çıkardığı Uluslararası Reklam Uygulama Esasları'dır.

Advertising is a mass communication technique which aims to influence human behaviour in a certain direction and increases the sales of a product or service. Advertising is, according to its most general definition, the announcement of facts or news to a certain category of people. In advertising, the people are informed by the communication means where, how and for which prices several goods and services can be found. Advertising started at the times when shopping started in the society and it continuously developed parallel to the deveolpment of comminacion means. With the invention of printing houses, the rhymed quatrains which were considered oral advertising left their place to newspapers which were lasting advertising media. The technological developments which occured in the 19th century were also used in production, industries were created, production increased. Mass Production produced the Mass Consume. In order to sell and to produce again the products that were manufactured, new markets were searched and thus advetising developed. As the production increased, competition grew too and this reflected on advertising. As a result of technological development, advertising media developed acquiring a different character. With the invention of radio and television new products were publcized and their sales were raised. The first one to advertise their products during the Ottoman Empire were the trader. In newspapers published in foreign languages, the European life and especially the French life was explained and the consume goods which were necessary for a modern life were shown. Advertising really developed in our country with the institution of the republican regime. The reform of the Turkish alphabet increased the number of lettered people, the number of newspapers increased and consequently, all those who wanted to advertise their products found a perfect ground for this. But as during the single political party period there was not a category of producers, there was only a national principle applied and neither competition nor advertising could develop on such a ground. When several political parties period started , there was a revival in the country's economy, the number of trader visibly increased and this had a positive effect on advertising. Especially after 1980, the increase of the consume, the increase and enlarging of the advertising field and the existence of competition were the causes of a such a development. When, starting from 1990, private TV channels began broadcasting, advertising found a perfect field to develop. After the heavy structure of State television and its control, private televisions became the ideal medium for the advertising world. Industrial revolution opened the door to mass production and products began to be manufactured in a very large range with regard to number and kind. The Mass Production gave way to a Mass Consume . Our society of today has the identity of a consume society. The only common point that links people from different races, colours, religions, political views and similar districtive factors is that they are all consumers. The identity of consumer is a universal identity. Although everybody is a consumer,the consumer conscience still has not developed enough. The consumer mass is the one that is mostly influenced by fake and misleading advertisements. At the time being it is much more diffucult to be a consumer than it was in the past. The large diversity of products makes the choice of the consumers more diffucult than ever. The product which the consumer will choose in such a large variety of products is the one that was advertised and the consumer directs his choice according to the information given to him in the advertisements. Therefore, the advertisements should give exact and correct information. Misleading and especially exagerated advertisements create a discontentment among the consumers and, as time goes by, such discontentment creates a loss of trust towards advertising. Advertisements should give true and exact information as true and exact information from an essential element of economy. Misleading information cause an economic wastfulness, this is the reason why advertising is being kept under control. There are two kinds of advertisement controls which are both applied in the world and in Turkey. The one is a legal control carried out in accordance with national laws while the other is a self-control which is being applied by the sector with a conscious responsibility. In this self-control the people who want an advertisement, the advertising agencies and the media controlling themselves without having to be submitted to legal controls. Self-control is much more effective than legal control, because those are preparing the advertisements are also those who are watching them more carefully. This is why the best and the fast way of control is the one that the advertising agencies apply to its own sector. In our country , advertising self-control is carried out by the Advertising Self-control Council (ROK=Reklam Özdenetim Kurulu). The ROK bases its activity upon the International Advertising Application Principles published by the İnternational Chamber of Commerce as it is the same in all countries which apply a self-control.
Keywords: Reklamcılık